The Future of Peaceful Nuclear Energy in the Middle East - Asia Ammar Abbas; Dr. Ruba Sahib Abd (Migration Letters, 2023)
Occupied region The Middle East matters big in strategies Globalism since contracts past, when enjoy with it This is amazing Region from value increasing from where the site vital and strategic weight And who He was Factor polarization powers Globalism different, So I became This is amazing Region pivot to conflict and rivalry international between powers regional and international terms you pay in its directions motives Different, and like the rest of the other regional regions, some countries in the region began to move towards the peaceful possession of nuclear energy in light of the rapid international developments, but there are factors influencing the peaceful possession of the countries of the Middle East such as spread and trade in addition to the international and regional risks and after the end of the war cold And it’s over polar binary did not finish with him the ban Nuclear but rather that nature this danger and its sources It has become miscellaneous or unknown Although from reservations that paid it Countries winning on arms nuclear what after the war cold in its arsenal nuclear unless that size Inventory Global for weapons nuclear still poses to threaten to ladder and security internationals. And it will be done search in this the topic on Two-way.